2020
DOI: 10.1186/s13023-020-01361-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in COL1A1/A2 and CREB3L1 are associated with oligodontia in osteogenesis imperfecta

Abstract: Background: Osteogenesis imperfecta (OI) is a heterogeneous connective tissue disorder characterized by an increased tendency for fractures throughout life. Autosomal dominant (AD) mutations in COL1A1 and COL1A2 are causative in approximately 85% of cases. In recent years, recessive variants in genes involved in collagen processing have been found. Hypodontia (< 6 missing permanent teeth) and oligodontia (≥ 6 missing permanent teeth) have previously been reported in individuals with OI. The aim of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…The Malmgren et al [ 4 ] study found hypodontia in 11% and oligodontia in 6% of their patients with OI. In that study, treatment with BPs was not considered; instead, the very high prevalence of hypodontia and oligodontia prompted the group to investigate whether mutations in genes other than those earlier associated with OI ( COL1A1 , COL1A2 , and CREB3L1 ) were responsible for the disturbances [ 27 ]. Except for the known variants, we were unable to identify any other mutual variant related to collagen type I that could explain the phenotype of OI associated with hypodontia/oligodontia.…”
Section: Discussionmentioning
confidence: 99%
“…The Malmgren et al [ 4 ] study found hypodontia in 11% and oligodontia in 6% of their patients with OI. In that study, treatment with BPs was not considered; instead, the very high prevalence of hypodontia and oligodontia prompted the group to investigate whether mutations in genes other than those earlier associated with OI ( COL1A1 , COL1A2 , and CREB3L1 ) were responsible for the disturbances [ 27 ]. Except for the known variants, we were unable to identify any other mutual variant related to collagen type I that could explain the phenotype of OI associated with hypodontia/oligodontia.…”
Section: Discussionmentioning
confidence: 99%
“…It is a missense mutation that is likely benign as predicted by software modeling. Other variants in this gene are associated with OI type III and are believed to be causal agents of the clinical features that are associated with this subtype, including dentinogenesis imperfecta 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss is a recognized extra-skeletal symptom of OI, most commonly observed in individuals with OI types I through IV. The assumed mechanism involves altered genes related to COL1A1 / COL1A2 , resulting in abnormal inner ear mineralization and otosclerosis . Hearing loss in people with OI is categorized into three types: conductive, sensorineural, and mixed.…”
Section: Oi Diagnosismentioning
confidence: 99%